The Implementation of the POE2WE Learning Model Assisted by PhET Simulation to Improve Conceptual Understanding of Grade XI Students at SMAN 1 Bukit Batu - Dzaidatul Masyhurah; Azhar; M. Nor (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to examine the effectiveness of the POE2WE (Predict, Observe, Explain, Elaborate, Write, Evaluate) learning model assisted by PhET simulations in improving students’ conceptual understanding of Newton’s laws. The research employed a quantitative approach with a quasi-experimental design, specifically a posttest-only nonequivalent control group design. The population consisted of 68 eleventh-grade students at SMAN 1 Bukit Batu, Indonesia, in the 2025/2026 academic year. The sample was divided into two groups: the experimental class, which received instruction using the POE2WE learning model assisted by PhET simulations, and the control class, which was taught using conventional methods. Data were collected through a posttest consisting of multiple-choice questions designed to measure seven indicators of conceptual understanding: interpreting, exemplifying, classifying, generalizing, inferring, comparing, and explaining. Data analysis was conducted using both descriptive and inferential statistics. The results of the descriptive analysis showed that the experimental class achieved a higher average score (70.32) categorized as good, compared to the control class (53.94) categorized as fair. Inferential analysis using the Mann–Whitney U test revealed a significance value of p = 0.000 (p < 0.05), indicating a significant difference between the two groups. These findings suggest that the implementation of the POE2WE learning model assisted by PhET simulations is effective in enhancing students’ conceptual understanding of Newton’s laws. Therefore, this study contributes to the development of interactive and technology-based physics learning strategies.